Familial Conn's syndrome. Issue 806 (December 1992) - London, N.; Swales, J.; Hollinrake, K.; Bell, P.; Heagerty, A.
Abstract : We describe the occurrence of primary hyperaldosteronism in two sisters. Although this is only the second published report of familial Conn's syndrome, it does have implications for the relatives of patients with Conn's syndrome and these are discussed.